Dermatomyositis related to the relapse of cervical cancer - Marta Stawczyk-Macieja; Aneta Szczerkowska-Dobosz; Izabela Błażewicz; Aleksandra Wilkowska; Roman Nowicki (Our Dermatology Online, 2015)
Dermatomyositis (DM) is a rare syndrome which belongs to the group of idiopathic inflammatory myopathies (IIM). The diagnosis of DM in adults is an indication for diagnostic evaluation towards malignancy. The exacerbation of clinical symptoms or laboratory markers of DM may indicate the relapse of neoplasm, therefore close follow-up visits of patients are obligatory. We present the case of a woman with a two-month history of progressive muscle weakness, dysphagia and oedemo-erythematous skin lesions limited to the face and trunk. The patient was diagnosed with DM associated with the relapse of cervical cancer.